Implied Volatility Sentiment: A Tale of Two Tails - Philip Stork; Luiz Félix; Roman Kräussl (Tinbergen Institute, 2017)
Low probability events are overweighted in the pricing of out-of-the-money index puts and single stock calls. This behavioral bias is strongly time-varying, and is linked to equity market sentiment and higher moments of the risk-neutral density. We _nd that our implied volatility (IV) sentiment measure, jointly derived from index and single stock options, explains investors' overweight of tail events well. When employed within a trading strategy, our IV-sentiment measure delivers economically signi_cant results, which are more consistent than the ones produced by the market sentiment factor. Out-of-sample tests on reversal prediction show that our IV-sentiment measure adds value over and above traditional factors in the equity risk premium literature.
Keywords: G12; G14; G17; 330; Sentiment; implied volatility skew; equity-risk premium; reversals; predictability